Analysis Of Working Environment And Career Development By Comparing Employee Engagement To Self Determination As Intervening Factors: (Study Of Millennial Employee Of Headquarters Of PT Jaminan Kredit Indonesia) - Tenri Angke Riliandra (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
This study examines the work engagement of millennial employees at PT Jamkrindo in 2022. The work engagement level at PT Jamkrindo is reported to be high and has shown an improvement compared to the previous year. However, there are key areas that need to be the company's top priority, namely providing an adequate work environment and ensuring certainty in employee career development. Self-determination acts as a mediation factor, allowing the research to explore and understand the internal processes that occur in the minds and emotions of individuals. How individuals respond to and interpret the work environment and career development personally can explain why and how work engagement is formed, involving psychological factors such as individual goals, values, and self-perceptions. Based on the research findings, the work environment at PT Jamkrindo has a significant impact on the level of work engagement. Similarly, career development at PT Jamkrindo also significantly influences the level of work engagement. The work environment at PT Jamkrindo has a significant impact on the level of work engagement through self-determination as a mediating factor. However, career development at PT Jamkrindo does not have a significant impact on work engagement through self-determination. There is potential for further in-depth research, including a deeper understanding of specific factors in the work environment and career development programs that have the most significant impact on millennial employees.